Lerion, Lerion, Tinta! forging public space - Agsalud, Mark Raymond C.
This research proposes the development of a printmaking technology-infused social space for children in an effort to forge public space „imageability‟ and identity collectivization in the city of Marikina. Through a two-fold site selection method, involving the conduction of a collaborative mental mapping with children and the use of Januchta-Szostak's site criteria for public space "imageability,‟ the researcher was able to locate the most optimal locations for showcasing public visual arts for children among the social spaces they themselves have identified. Printmaking was the proposed public visual art intervention due to its inexpensive, resourceful, and collaborative nature. The collaborative mental mapping that was conducted emphasized the determination of positive spaces, or spaces where the children participants socialize and interact. These spaces are particularly important in the fostering and cultivation of the values of Filipino personhood or pakikipag-kapwatao. Having these social spaces as the primary sites for the proposed design solution would further instill a strong sense of belonging among the Marikeño youth, encouraging them to be more creative and playful and as a result, deepen the culture of the city. All of which, are in line with the city‟s effort to strengthen their existing local cultural programs and to pave the way towards the sustainability and collective prefiguration of their identity into the future.